Protection of Data Privacy in The Era of Artificial Intelligence in The Financial Sector in Indonesia - Sinta Dewi Rosadi; Siti Yuniarti; Rizki Fauzi (Bank Indonesia, 2022)
The concept of privacy has broad ramifications, and it is implemented in a number of disciplines, ranging from philosophy to computer science, political science and legal science. This paper covers the impact of artificial intelligence on privacy protection, especially in the finance sector. Privacy protection is associated with control over information about personal data, also known as private information. This research is a normative legal research of analytical nature, and it is conducted by studying and interpreting theoretical matters relating to the principles, conceptions, doctrines and legal norms pertaining to the problems. The results of this research show that the concept of privacy in the era of artificial intelligence in Indonesia is best achieved by combining comprehensive rules with self-regulation to serve as a balancing agent between laws and technology in order to control and fulfill the protection of personal data in the era of artificial intelligence.